VD_FINDINFO Décision / 2015 / 824 vom 5. November 2015 - VD Tribunal cantonal (2015)
CAS DE SÉQUESTRE, SUPPRESSIONEN GÉNÉRAL, PROPORTIONNALITÉ | 69 CP, 263 al. 1 let. a CPP (CH), 263 al. 1 let. d CPP (CH)